Sol e Sombra: o Café do Maciço de Baturité Numa Perspectiva Ecológica e Socioeconômica. - Alcântara, Selma Maria Peixoto (2009)
The coffee plant (Coffea arabica) originally comes from African territory. It was introduced to Brazil in 1727 starting out from Rio de Janeiro, in the Atlantic Forest, where coffee-growing was better adapted and it was established as an important economic activity for the colonial exploitation pattern, based on monoculture, slave force and extensive property. Thus starts the history of an activity renowned as economically important for the country and part-responsible for the devastation left by that activity in the regions where it was developed. Such destruction followed a logic of relations between society and nature based on the former dominating the latter. The use and occupation of Brazilian territory in the eighteenth century were based on that logic. The consequences of this can be seen in agriculture, mainly based on fire clearance and deforestation practices in the plantations. In Ceará it was not different. Nevertheless, in the areas where coffee-growing was developed this practice was impracticable, as the prevailing system of cultivation relied on the association of the coffee plant with others species, particularly ingazeira (Inga bahiensis Benth.). The main objective of this study is to analyze the importance of coffee-growing activities in Maciço de Baturité-Ceará and its social relationship with production, from the 1970s onwards. It seeks to find out about the importance of this activity as a degradation factor or conservation of environmental patrimony in the ecological, socio-economic perspective. To reach this objective, there was an engagement to comprehend how this activity was developed historically in the region, to comprehend the culture arisen around the coffee-growing and the work-relationship established within the farming space.